Outcome of Titanium Elastic Intramedullary Nail in the Treatment of Shaft of Femur Fracture in Children - Khan, J.A.; Singh, G.P.; Pandey, A. (Kathmandu University Medical Journal, 2017)
Background Femoral-shaft fractures are among the most common fractures of the lower extremity in children. There are several different options for treating femoral-shaft fractures in children. Elastic stable intramedullary nailing (ESIN) has become the standard treatment for fractures of shaft of femur in children for reasons including mini-invasive surgery, no need for casting, early mobilization and discharge as well as growing concerns toward cost-effectiveness. Objective To demonstrate the effectiveness of intramedullary fixation of fracture shaft of femur in skeletally immature children using the titanium elastic intramedullary nails. Method Forty children who underwent fixation with titanium intramedullary nails because of fracture of shaft of femur (Winquist and Hansen type 1 and 2) were reviewed. There were 60% male and 40% female patients and mean follow-up was six months. Time of union, deformity at fracture site, limb length discrepancy, knee range of motion and complications were assessed. Result Average age of the patients was 5.17 years (range 3 to 10). All patients achieved complete healing at a mean 12.8 weeks (range 10 to 20 weeks). Average limb length discrepancy was -0.16 cm (range -1.0 to 1.1 cm) average knee range of motion was 137.55 degrees (range 118 to 152 degrees). Complications were recorded in 13 (31.7%) patients and included: Five malunion which did not show any deformity or functional impairment and eight superficial wound infections which were healed after removal of nail. All patients were active as their pre injury levels at six months follow up. Conclusion Elastic stable intramedullary nailing is the method of choice for the simple pediatrics fracture shaft of femur, as it is minimally invasive and shows good functional and cosmetic results. It allows short hospital stay and quick recovery from pain and is cast-free.